Regarding Conceptions and Practices of Education in the Solidarity Sector of Medellín, Colombia - Amariles Mejía, Cristina (Cooperativismo & Desarrollo, 2015)
Introduction: The question of educational conceptions and practices in the solidarity sector of Medellín is an initiative for listening to the voice of the people and organizations who have developed this type of processes. Methodology:This research has a hermeneutic approach aimed at understanding the text (interviews) of key individuals in the social and solidarity economy sector in Medellín. Results: The article is divided into four parts: the first provides context about the solidarity sector in Medellín and the research as such; the second focuses on conceptions of education that arise from analysis of the interviews; the third is based on the solidarity education practices demonstrated by those interviewed, generating a typology of practices, depending upon the approach and the fundamental place (or lack of one) in the solidarity economy sector of Medellín and, finally, the conclusions. Conclusions: There are two ways of seeing education in the solidarity economy sector: first of all, in relation to internalstrengthening of the sector and its educational initiative for its promotion and consolidation; and secondly, in coordination with the social movements and initiatives for transformation of the society.
Keywords: cooperativism; education; solidarity sector; solidarity.